2004
DOI: 10.1111/j.1479-828x.2004.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostitution and other cofactors in preinvasive and invasive lesions of the cervix

Abstract: First sexual experience before 20 years of age, cigarette smoking and HPV infection were high-risk factors for preinvasive and invasive lesions of the cervix in Venezuelan FSW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
(25 reference statements)
0
2
1
Order By: Relevance
“…As predicted in the ''Inverse Care Law'' (13) , those in need are less likely to receive the care: 9.8% (23/235) FSW had preinvasive lesions (CIN I-CIN III) in contrast to 5.5% (395/3601) of the Hong Kong general population (14) . Comparing to other studies of abnormal smears in sex workers, it is much higher than those found in Singapore (5.6%) (15) and Austria (6.3%) (16) , but more comparable to a startlingly high prevalence in Venezuela (13.9%) (17) . Moreover, the regression analysis showed that the place of origin (local or nonlocal FSW) was the single most important risk factor for CIN II-III-this independent variable was unlikely a confounding factor for whether cervical smear had ever been done as this has been controlled.…”
Section: Discussioncontrasting
confidence: 66%
“…As predicted in the ''Inverse Care Law'' (13) , those in need are less likely to receive the care: 9.8% (23/235) FSW had preinvasive lesions (CIN I-CIN III) in contrast to 5.5% (395/3601) of the Hong Kong general population (14) . Comparing to other studies of abnormal smears in sex workers, it is much higher than those found in Singapore (5.6%) (15) and Austria (6.3%) (16) , but more comparable to a startlingly high prevalence in Venezuela (13.9%) (17) . Moreover, the regression analysis showed that the place of origin (local or nonlocal FSW) was the single most important risk factor for CIN II-III-this independent variable was unlikely a confounding factor for whether cervical smear had ever been done as this has been controlled.…”
Section: Discussioncontrasting
confidence: 66%
“…In female sex workers (FSWs), risks associated with cervical cancer include early age at first sexual intercourse, multiple sexual partners, and cigarette smoking. Moreover, abnormal cytologic results, human papillomavirus (HPV) infection with high‐risk strains, and HPV‐related cervical disease are significantly more prevalent among FSWs than in control groups [1,4–7]. Thus, beyond STD prevention, it is important to face the issues regarding cervical cancer prevention.…”
Section: Introductionmentioning
confidence: 99%
“…These are found in females of a variety of insect species and other taxa (Carayon 1966, Carayon 1977Eberhard 1985). In some species they occur very frequently or even regularly (van Damme et al 1998;Sota and Kubota 1998;Fraser et al 1999;Crudgington and Siva-Jothy 2000;Blanckenhorn et al 2002;Nunez et al 2004;Beani et al 2005;Kamimura 2007). In humans, micro traumata in the mucus layer of the genitalia that arise from sexual intercourse, if rarely investigated (Fraser et al 1999;van Damme et al 1998;Nunez et al 2004) are one of the main entrance areas for STDs into the body.…”
Section: External and Sexually Transmitted Microbesmentioning
confidence: 97%